Hubungan Indeks Massa Tubuh dengan Kadar Gula Darah Post Prandial - Br. Siahaan, Thresia Deswinta; Pasaribu, Sumihar; Sitompul, Donald F (Universitas Methodist Indonesia, 2020)
Background : Obesity is a disorder or disease characterized by excessive accumulation of fatty tissue in the body. Obesity occurs because of an imbalance between incoming and outgoing energy. Obesity / overweight has become a global pandemic worldwide and is declared by the World Health Organization as the biggest chronic health problem. Blood glucose levels in normal conditions tend to increase slightly, but after reaching the age of 50 years, the increase is progressive, especially for people who do not do physical Activity Normal blood glucose levels are between 70-110 mg/dl after fasting for 8 hour and 2 hour after eating, the blood glucose level should be below 200 mg/dl. Blood glucose levels increase after eating because there is a supply of glucose from the food consumed. Purpose Of The Study : To determine the relationship between body mass index and postprandial blood sugar levels. Research Methods : This types of research is research using the literature method. Result : From several research articles that explain that there is a relationship between body mass index and postprandial blood sugar levels.